Development of a novel variable stiffness device based on magneto-rheological elastomers for soft robots - Atakuru, Taylan. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
One of the biggest challenges in soft robotics is the variability and controllability of stiffness. Compliance is required for soft robots to enable dexterity and secure interactions with the environment, whereas rigidity is required to transmit forces when necessary. Stiffness variation of soft robots has been achieved through stiffening methods such as antagonistic arrangement of active elements, jamming by vacuum, and viscosity change under magnetic field. The methods can be compared in terms of speed of stiffening and destiffening, modes of stiffening, and stiffness variation. Magnetorheological elastomers (MREs) are effective in response time and suitable for different stiffening modes, such as bending, tension, and compression. However, stiffness variation data can only reach high values if a very high magnetic field is applied. Jamming-based methods appeal due to fabrication, low cost, and stiffness variation. However, the speed of this technology is not particularly remarkable. In addition, it requires an external membrane, creating design complications for system integration. No research that utilizes both methods simultaneously is found in the soft robotics literature. In this thesis, a hybrid method is proposed that combines a jamming-based approach with a viscosity-based one for stiffening of soft robots. The proposed method is innovative because stiffness variation is boosted by exploiting the advantages of magnetic jamming of MREs. In order to prove the proposed method, a number of steps was taken. First, the bending behavior of MREs is analytically, numerically, and experimentally investigated to analyze the effect of volume fraction of magnetic particles on stiffness variation. Second, a multi-layer jamming structure consisting of MRE layers and two flexible Neodymium-Iron-Boron (NdFeB) magnets is developed to investigate the unique mechanics of magnetic jamming of MRE sheets exploring stiffness change both due to jamming and variable viscoelasticity. Third, a fiber jamming structure consisting of MRE fibers and a flexible NdFeB magnet is developed and integrated into a soft robot, the STIFF-FLOP manipulator. Stiffening tests are performed on the manipulator to prove the concept of magnetic jamming of MRE fibers. Results show that stiffness gain in bending and compression is achieved with the proposed method. Finally, a possible implementation of electronically-controlled magnetic jamming and stiffening is demonstrated on the manipulator which is embedded with electro- permanent magnets. The findings of this thesis show that the proposed hybrid stiffening method combining jamming with viscoelasticity modification is a promising approach to achieve variable and controllable stiffness in soft robots.
Keywords: Robots.; Elastomers.